Life, Purpose, And Spiritual Destruction In The Novel “Martin Iden” (Eurasian Research Bulletin, 2025)
This article analyzes the conflicts of not only one person, but also an entire era and society through the inner world, dreams, and struggles of the main character of Jack London’s novel “Martin Eden”. Martin’s tragedy is that a person is expected to be happy after achieving the lofty goals he has set for himself. However, life does not always go, as he wants. Martin’s iron will, dedication to work, and ultimately his loss of himself in a meaningless society are shown as a symbol of a person who has lost himself. Through this, the work deeply analyzes the issues of self-discovery, conflict with society, depression, and loneliness. The article also draws warning and thought-provoking conclusions for modern youth